Návrh výroby držáku madla - Ryšavý, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Ekonomický a technologický rozbor možných způsobů výroby skutečné součástí. Základní teoretické znalosti vybraných výrobních metod a jejich uplatnění v praxi. Rozdělení výrobních metod pro různé výrobní série součásti pomocí ekonomického zhodnocení.

Economic and technological analysis of possible methods of production real part. The basic theoretical knowledge of selected production methods and their application in practice. The division of production methods for various production series of part using economic evaluation.
Production of handrail holder
Keywords: Řezání; laser; vodní paprsek; plazma; plošné tváření; stříhání; ohýbání; sdružený nástroj; přesnost; jakost plochy; ekonomický rozbor.; Cutting; laser; water jet; plasma; sheet metal forming; shearing; bending; combined tool; accuracy; surface quality; economic analysis.